Laser doppler imaging as additional monitoring after digital replanting: A prospective study. Issue 6 (14th March 2018) - Schmid, Marc; Seyed Jafari, S. Morteza; Haug, Luzian; Surke, Carsten; Hunger, Robert E.; Van De Ville, Dimitri; Juon Personeni, Bettina; Shafighi, Maziar; Voegelin, Esther
Abstract : Background: Despite various exisiting monitoring methods, there is still a need for new technologies to improve the quality of post‐operative evaluation of digital replantation. The purpose of the study is using a laser Doppler imaging device (Easy‐LDI) as an additional tool to assess perfusion. In this method, the changes in the frequency of the laser ligth provide information regarding perfusion of the monitored tissue. Patients and Methods: This study included seven patients (10 fingers; age of patients: 21–57 years) who suffered from a total ( n = 6) or subtotal amputation ( n = 4) due to accidents. In addition to hourly standard monitoring with clinical evaluation and skin thermometry, revascularized fingers were hourly monitored with Easy LDI for 48 h. Results: LDI measurement values ranged between 0.8 and 223 (mean 90.62 ± 21.42) arbitrary perfusion units (APU). The mean LDI values before and after revascularization were 7.1 ± 2.85 and 65.30 ± 30.83 APU, respectively. For the successful revascularized fingers (8 of 10 fingers) values from 19 to 223 APU (mean 98.52 ± 15.48) were demonstrated. All of the replants survived, but due to venous occlusion two digits required revision 12 and 35 h after revascularization, respectively. In the two cases, Easy‐LDI also showed a constant and slow decline of the perfusion values. Furthermore, Pearson normalized correlation coefficient showed a positive significant correlation between temperatures of the replants and LDI‐values ( P < .001, r = +0.392) and a negative significant correlation between Δtemperature and LDI‐values ( P < .001, r = –0.474). Conclusion: The LDI‐device might be a promising additional monitoring technique in detection of perfusion disturbance in monitoring digital replantations.